2018
DOI: 10.1093/jamia/ocy050
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for assessing the quality of mHealth apps: a systematic review

Abstract: There is a wide heterogeneity in assessment criteria for mHealth apps. It is necessary to define the exact meanings and degree of distinctness of each criterion. This will help to improve the existing tools and may lead to achieve a better comprehensive mHealth app assessment tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 45 publications
5
174
0
7
Order By: Relevance
“…A recent review on criteria of assessing the quality of mHealth (mobile health) apps concluded: ‘There will never be a complete and perfect mHealth app assessment criteria because these criteria must apply to apps that are changing in development continuously’ 20. A Canadian-based effort that gathered diverse mental health stakeholders, including patients, noted that they were not able to find a single scale or framework that adequately addressed their needs 21.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review on criteria of assessing the quality of mHealth (mobile health) apps concluded: ‘There will never be a complete and perfect mHealth app assessment criteria because these criteria must apply to apps that are changing in development continuously’ 20. A Canadian-based effort that gathered diverse mental health stakeholders, including patients, noted that they were not able to find a single scale or framework that adequately addressed their needs 21.…”
Section: Discussionmentioning
confidence: 99%
“…However, they only provide the crawled app store information and not calculated results. Regarding the second category, summaries that can be used as a very good starting point can be found in [22]- [24] or works that address particular aspects [25]- [27] or the development of rating tools [28], [29]. Furthermore, works can be found that deal with the userfriendly development of mHealth apps, thus increasing their quality by design [30]- [32].…”
Section: Related Workmentioning
confidence: 99%
“…A recent systematic review identified 23 different published criteria for assessment of mHealth apps. 38 Furthermore, many apps popular with patients are not seen as high quality by clinicians. 32,39 It is important that medical professional societies and clinicians who recommend apps often engage patients in the decision-making process.…”
Section: How Can Clinicians Support Patients In Obtaining Value From mentioning
confidence: 99%